2013
DOI: 10.1002/eat.22240
|View full text |Cite
|
Sign up to set email alerts
|

Upward appearance comparison and the development of eating pathology in college women

Abstract: These findings suggest that the extent of upward appearance comparison may be useful for identifying college women at particular risk for developing clinically significant disordered eating symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 17 publications
3
43
0
Order By: Relevance
“…This is concerning because these upward appearance comparisons lead women to feel dissatisfied with their bodies and be more motivated to engage in compensatory eating behaviors (Arigo, Schumacher, & Martin, 2014). Research has demonstrated a link between upward appearance comparisons and increases in body dissatisfaction, drive for thinness, bulimia, and negative mood (Bailey & Ricciardelli, 2010;Ridolfi, Myers, Crowther, & Ciesla, 2011;Tiggemann, Polivy, & Hargreaves, 2009;Van den Berg & Thompson, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is concerning because these upward appearance comparisons lead women to feel dissatisfied with their bodies and be more motivated to engage in compensatory eating behaviors (Arigo, Schumacher, & Martin, 2014). Research has demonstrated a link between upward appearance comparisons and increases in body dissatisfaction, drive for thinness, bulimia, and negative mood (Bailey & Ricciardelli, 2010;Ridolfi, Myers, Crowther, & Ciesla, 2011;Tiggemann, Polivy, & Hargreaves, 2009;Van den Berg & Thompson, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This scale has been used with racially and ethnically diverse women. 22 Higher mean scores indicate a greater tendency to engage in appearance-related comparisons (current sample Upward a 5 .94; Downward a 5 .91).…”
Section: Upward and Downward Appearance Comparisons The 18-item Upwamentioning
confidence: 83%
“…In line with these considerations, studies found that women with eating disorders engaging in upward appearance-based comparisons were at higher risk for body dissatisfaction and disordered eating [21, 22]. For men, a strong tendency to compare oneself to others exacerbated the relationship of body dissatisfaction and drive for muscularity [23].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, body schemas have been provoked through questions regarding body image, commercials showing models with “ideal” bodies, or ads for beauty products [28]. Although models in magazines activate body schemas, it could also be assumed that they initiate social comparison processes, since for the investigation of comparisons similar procedures have been used [21, 22]. Another approach postulated that body exposure by mirror confrontation can provoke (negative) body schema [29].…”
Section: Introductionmentioning
confidence: 99%